18S rDNA Polymerase Chain Reaction and Sequencing in Onychomycosis Diagnostics - Walberg, M; Mørk, C; Sandven, P; Jorde, AT; Bjørås, M; Gaustad, P (Acta dermato-venereologica, 2006)
Diagnostic approaches to onychomycosis have traditionally been based on a combination of culture and microscopy. In the present study clinical specimens from 346 patients with suspected onychomycosis were analysed by 18S polymerase chain reaction (detection) followed by sequencing and subsequent database search (identification) in parallel with routine culture on agar (detection and identification). In 49 samples Trichophyton rubrum was identified by culture and sequencing. In 67 additional culture negative samples, a positive dermatophyte sequence was obtained (T. rubrum in 54, T. mentagrophytes in 5, and T. species in 8 samples). Fifteen samples cultured positive while no sequence was obtained. Two hundred and seven samples were negative by culture as well as by sequencing. Nails from 10 healthy controls were negative by culture and sequencing. In conclusion, the number of specimens that were positive by polymerase chain reaction was more than double the number that were positive by culture alone.